Return to theatre for post-tonsillectomy haemorrhage in children has not fallen with increased use of plasma ablation tonsillectomy: a retrospective analysis of 359,241 tonsillectomies in 15 years of United Kingdom Hospital Episode Statistics - Jeremy P. Reid; Thomas Beech; Jameel Muzaffar (PLoS ONE, 2025)
Introduction Plasma ablation tonsillectomy has rapidly increased in popularity and is now the most popular technique in children. This study aims to evaluate the impact of plasma ablation tonsillectomy on the incidence of post-operative haemorrhage requiring surgical intervention in children, a complication affecting patient safety and healthcare resource utilisation. Methods 15 years (2009/10–2023/24) of Hospital Episode Statistics for children 14 years or under, capturing all tonsillectomies in NHS England hospitals was analysed. The proportion performed by plasma ablation and rate of surgical intervention for post-tonsillectomy haemorrhage were calculated. Pearson’s Correlation Coefficient was used to statistically analyse the relationship. Results Data from 359,241 tonsillectomies was analysed. The proportion of tonsillectomies performed with plasma ablation has grown yearly from 7% in 2009/10–47% in 2023/24. A change in trend in the rate of return to theatre for haemorrhage control was not identified across the study period. (Pearson Correlation Coefficient −0.15, p = 0.59). Conclusion These findings do not support a superior safety profile of plasma ablation tonsillectomy with regard to post-operative haemorrhage. However, due to dataset limitations it was not possible to analyse intracapsular and extracapsular procedures independently. There remains a need for continued evaluation of tonsillectomy techniques to inform optimal surgical practice.